A randomized multicenter trial comparing the XIENCE everolimus eluting stent with the CYPHER sirolimus eluting stent in the treatment of female patients with de novo coronary artery lesions: The SPIRIT WOMEN study. - Anna Franzone; Serge Zaugg; Raffaele Piccolo; Maria Grazia Modena; Ghada W Mikhail; Josepa Mauri Ferré; Ruth Strasser; Liliana Grinfeld; Dik Heg; Peter Jüni; Stephan Windecker; Marie-Claude Morice (PLoS ONE)
Background The comparative performance of different drug-eluting stents (DES) among female patients has not been assessed in a randomized manner. Objectives The SPIRIT Women Clinical Evaluation trial compared the durable polymer everolimus-eluting XIENCE stent (DP-EES) with the durable polymer sirolimus-eluting Cypher stent (DP-SES) in women undergoing percutaneous coronary intervention (PCI). Methods A total of 455 female patients with stable CAD were randomly assigned to receive DP-EES (n = 304) or DP-SES (n = 151). The powered angiographic outcome of the trial was in-stent late lumen loss (LLL) at 9 months after the index procedure. Secondary angiographic end points included in-segment LLL, in-stent and in-segment binary restenosis and percent diameter stenosis. The primary clinical outcome was a composite of all-cause death, myocardial infarction (MI) or target vessel revascularization (TVR). Results At 9-month follow-up, in-stent LLL was 0.19±0.38 mm and 0.11±0.37 mm in patients assigned to DP-EES and DP-SES, respectively. The one-sided upper 95% CI of the difference in in-stent LLL between the groups of 0.08 mm was 0.15 and therefore within the pre-specified non-inferiority margin of 0.17 mm (p for non-inferiority = 0.013). However, the test for superiority showed a borderline significant difference in terms of LLL between DP-EES and DP-SES (p for superiority = 0.044). There were no significant differences in binary restenosis (2.0% vs. 0.72%, p = 0.44) and percent diameter stenosis (14.97±12.17 vs. 13.36±10.82, p = 0.19). The rate of definite stent thrombosis at 12 months was lower in patients treated with DP-EES (0% vs. 2.0%, p = 0.036). Conclusions Among women undergoing PCI, DP-EES was associated with a small but probably clinically relevant increase in in-stent LLL at 9 months as compared to DP-SES and with a lower risk of definite stent thrombosis at 12 months. Trial registration ClinicalTrials.gov NCT01182428. https://clinicaltrials.gov/.